Captain Cook upon Changing Seas: Indigenous Voices and Reimagining at the British Museum. Issue 3 (2nd July 2020) - McLaren, Annemarie; Clark, Alison
ABSTRACT: This article reviews the British Museum exhibition, Reimagining Captain Cook: Pacific Perspectives, 29 November 2018–4 August 2019. It situates the exhibition within a global context of exhibitions held around the 250th anniversary of Cook's first voyage, and critically considers its attempt to reframe dominant narratives surrounding Cook, his voyages and more broadly the colonization of the Pacific through a focus on Pacific Islander perspectives within a changing museum sector.